Nurses’ Vigilance in Care and Patient’s Readiness for Hospital Discharge: A Correlational Study - Khaledian, Nadere; Mahmoudi, Mokhtar; Kamyari, Naser; Vatandost, Salam (Advances in Nursing & Midwifery, 2025)
Introduction: Patient’s Readiness for Hospital Discharge (RHD) is one of the affecting factors on implications after being discharged. So, identifying variables related to RHD is important. Nurses’ Vigilance in Care may effect on RHD. To determine the correlation between Nurses’ Vigilance in Care and Patient’s readiness for Hospital Discharge. Methods: In this correlational study, 351 discharged patients in different wards of three educational hospitals of Kurdistan University of Medical Sciences in Sanandaj city were selected with Convenience Sampling. Before discharge, demographic form, the questionnaire of RHD and the questionnaire of Nurses’ Vigilance in Care from the patient’s point of view. The analysis of the data was conducted by the SPSS version 21 application. Frequency, Mean and standard Deviation for descriptive and spearman test to correlational was used. Results: The findings reveal the overall score of Nurses’ Vigilance in Care was at the intermediate level at 61.84±9.91, while the overall score of the patient’s RHD was at a poor level at 47.6±2.58. The results showed that nurses Vigilance in Care, higher education, being employed, having family support, and having the ability to self-care were predictor of RHD. Conclusions: The patients’ RHD and Nurses’ Vigilance in Care weren’t in a desirable, both. Furthermore, their positive significant correlation indicates that planning is required to raise Nurses’ Vigilance in Care to increase patients’ RHD.